Guesswork and guilt—the mind of a suicide. Issue 2 (6th December 2004) - Berry, P
Abstract : This is an imagined dialogue between the ghost of a young suicide and an old schoolfriend. The living discussant, a doctor now, regrets that he did not realise how deeply troubled his friend was, and wants to know if and in what way he could have dissuaded the depressed schoolboy from his irrevocable decision. The ghost, however, confident in death, free from mental anguish, challenges the doctor's presumptions. What right does he, does society have, to stop, detain, dissuade, and "cure" those who wish to kill themselves? The issues of sanity, free will, and societal judgment are explored in an encounter that can never take place, but which sheds light on the thought processes of the suicidal.